Disaster Risk Reduction Learning Model in the School Curriculum - Kamarudin, Syamsu A (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research discusses the "Disaster Risk Reduction Learning Model in the School Curriculum," which shows a positive impact on increasing student awareness, material integration, active involvement, teacher training, and relevant curriculum development. The research results indicate that this learning model is successful in instilling a deep understanding of disaster risk and the necessary mitigation steps, so that students become more sensitive and proactive in dealing with potential threats in their environment. Integrating disaster risk reduction material with other subjects such as science and geography helps students see relationships between disciplines and apply concepts in a broader context. Active involvement of students through interactive methods, such as simulations and role-playing, improves social and collaboration skills that are essential in disaster management. Effective teacher training plays an important role in the implementation of this model, enabling teachers to deliver material in ways that are innovative and responsive to student needs. In addition, developing curricula adapted to local conditions allows students to understand and overcome specific challenges in their communities. The evaluation and feedback system implemented provides valuable information for students and teachers, supporting continuous improvement in the teaching and learning process. Overall, this research confirms that the disaster risk reduction learning model contributes significantly to students' preparedness and resilience in facing disasters.